Molecular mechanisms underlying metabolic syndrome: the expanding role of the adipocyte. Issue 10 (13th July 2017) - Armani, Andrea; Berry, Alessandra; Cirulli, Francesca; Caprio, Massimiliano
ABSTRACT: The metabolic syndrome (MetS) is defined as a cluster of 3 or more metabolic and cardiovascular risk factors and represents a serious problem for public health. Altered function of adipose tissue has a significant impact on whole‐body metabolism and represents a key driver for the development of these metabolic derangements, collectively referred as to MetS. In particular, increased visceral and ectopic fat deposition play a major role in the development of insulin resistance and MetS. A large body of evidence demonstrates that aging and MetS share several metabolic alterations. Of importance, molecular pathways that regulate lifespan affect key processes of adipose tissue physiology, and transgenic mouse models with adipose‐specific alterations in these pathways show derangements of adipose tissue and other metabolic features of MetS, which highlights a causal link between dysfunctional adipose tissue and deleterious effects on whole‐body homeostasis. This review analyzes adipose tissue‐specific dysfunctions, including metabolic alterations that are related to aging, that have a significant impact on the development of MetS.—Armani, A., Berry, A., Cirulli, F., Caprio, M. Molecular mechanisms underlying metabolic syndrome: the expanding role of the adipocyte. FASEB J. 31, 4240–4255 (2017). www.fasebj.org